APPLICATION METHODS TO INCREASE OF ROLE PLAYING ON LEARNING MATERIALS PRESERVING NKRI (PENERAPAN METODE ROLE PLAY UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI MENJAGA KEUTUHAN NKRI) - -, Mahfudin (Prodi Teknologi Pendidikan, 2016)
Abstract. Uncertainty in the nation's economy, the impact of globalization as well as various crises and disasters are problems that may lead to national disintegration which make few groups want to secede from NKRI. All these problems unilaterally are evidences of the unreliability of civic education learning as a subject that mandates to maintain the integrity of NKRI, not in the macro scope but in giving civic education as early as possible from the elementary school. The learning outcomes of civic education learning do not only include the acquisition of knowledge, but more to the acquisition of feeling and behavior. Consequently, in the pre-cycle, the researcher found difficulties to integrate the two domains, which made the learning outcomes below the mini-mum mastery criteria, students’ behavior lacking the feeling of love to their homeland and stu-dents’ motivation in learning low. To solve the problems, the researcher used role play method and as a result, after two cycles, students’ learning outcomes increased. The percentage of stu-dents’ minimum mastery criteria increased from 52% (score 75) to 69% in cycle I and 96% in cycle II. In addition, the students’ were more motivated in learning, followed ceremony in an or-derly manner, and behaved in ways that reflect the love of homeland. It can be concluded that ap-plying role play method in the lesson of preserving the integrity of NKRI at Grade V SDN Cilengkrang North Sumedang Regencey, students’ learning outcomes could be improved.Keywords: Role Play Method, Civic Education Learning, Integrity of The Unitary State of The Republic of IndonesiaAbstrak. Ketidakpastian kondisi perekonomian bangsa, pengaruh globalisasi serta berbagai krisis dan bencana merupakan permasalahan yang merujuk ke arah disintegrasi bangsa. Sehingga segelintir kelompok ingin memisahkan diri dari NKRI. Semua permasalahan diatas secara sepihak merupakan suatu bukti ketidak mempanan pembelajaran PKn sebagai mata pelaja-ran yang mengamanatkan untuk menjaga keutuhan NKRI, tetapi bukan dari kasus makro melain-kan harus dimulai sedini mungkin dari lingkungan sekolah dasar. Hasil belajar PKn tidak hanya menuntut penguasaan pengetahuan, tetapi lebih kepada perasaan dan perilaku. Maka dari itu ketika pra siklus penulis mengalami kesulitan untuk memadukan ranah tersebut sehingga hasil belajar di bawah KKM, perilaku siswa akan rasa cinta tanah air kurang melekat, bahkan semangat belajar kurang termotivasi. Maka dengan itu, penulis merancang sebuah pembelajaran dengan metode Role Play. Alhasil dengan dua kali tindakan hasil belajar siswa pun meningkat. Persentase ketun-tasan belajar siswa mengalami peningkatan dari 52% yang mencapai nilai KKM yaitu 75. Pada siklus I meningkat mejadi 69% dan siklus II 96%. Siswa pun belajar dengan semangat, mengikuti upacara dengan tertib, dan berperilaku yang mencerminkan cinta tanah air. Maka dari itu dengan menerapkan metode Role Play pada pembelajaran pentingnya menjaga keutuhan NKRI di kelas V SDN Cilengkrang Kecamatan Sumedang Utara hasil belajar siswa dapat meningkat.Kata Kunci: Metode Role Play, Pembelajaran PKn, Keutuhan NKRI